Design of charging unit uninterruptible power supply: article / Mohd Hanif Marzukhi - Marzukhi, Mohd Hanif (2014)
This project a design of Charging Unit or rectifier for uninterruptible power supply by using PWM switching technique. These basic conversion performances are implemented by using MATLAB SIMULINK (MLS). Selected switching frequency is 9 kHz, 6 kHz and 4 kHz to investigate the actual performance of the battery charger. MATLAB SIMULINK results are show the accuracy of modeling.